Construções de sentidos em disputa: o caso Duda Reis e Nego do Borel como acontecimento midiatizado - Garcia, Renata do Nascimento (Universidade do Vale do Rio dos Sinos, 2024)
In this dissertation, we address the dispute of meanings based on the case of Duda Reis and Nego do Borel as a mediatized event. The relationship between these two celebrities was marked by an intense media sphere, in the context of Brazilian media. This research seeks to describe and understand how the case is constituted. To do so, we rely on journalistic reports, as well as comments and publications from collectives. The Duda Reis and Nego do Borel case, in our research, consists of a time frame of 16 months, - June 2020 to March 2021. As for our analysis, we rely on the descriptive methodological perspective of four moments, which are named as follows: Rejection and Family Conflicts, The Mediatized Breakup, The Reality Show and The Legal Conflict. Choosing moments helps us as methodological references. We follow a process that analyzes each of the moments, understanding the operations that describe each of these moments. As theoretical support, we rely on sources that discuss the following notions: Mediatization (Gomes, 2016), Mediatized Case (Weschenfelder, 2019), circulation (Rosa, 2016; Fausto Neto, 2018) and celebrities (Simões, 2012). From the analysis, we realized the power of collectives in the narration and construction of meanings based on the mediatized case.
Keywords: Midiatização; Circulação; Celebridades; Coletivos; Caso midiatizado; Mediatization; Circulation; Celebrities; Collectives; Mediatized case; ACCNPQ::Ciências Sociais Aplicadas::Comunicação